2013
DOI: 10.1371/journal.pone.0060942
|View full text |Cite
|
Sign up to set email alerts
|

Structural Lability of Barley Stripe Mosaic Virus Virions

Abstract: Virions of Barley stripe mosaic virus (BSMV) were neglected for more than thirty years after their basic properties were determined. In this paper, the physicochemical characteristics of BSMV virions and virion-derived viral capsid protein (CP) were analyzed, namely, the absorption and intrinsic fluorescence spectra, circular dichroism spectra, differential scanning calorimetry curves, and size distributions by dynamic laser light scattering. The structural properties of BSMV virions proved to be intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
(45 reference statements)
1
21
0
Order By: Relevance
“…Two lateral inter-subunit salt bridges are also present in TMV ( Figure 6 ), CGMMV, RMV, and HLSV, but the ion pairs forming them vary between the different viruses (TMV/RMV Arg113-Asp115 and Arg122-Asp88; CGMMV Arg113-Asp115 and Arg77-Glu130; HLSV His122-Asp88 and Arg31-Glu81) ( Tewary et al., 2011 ). It is possible that the reduced number of inter-subunit interactions in BSMV may explain its lower stability compared with TMV virions ( Makarov et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two lateral inter-subunit salt bridges are also present in TMV ( Figure 6 ), CGMMV, RMV, and HLSV, but the ion pairs forming them vary between the different viruses (TMV/RMV Arg113-Asp115 and Arg122-Asp88; CGMMV Arg113-Asp115 and Arg77-Glu130; HLSV His122-Asp88 and Arg31-Glu81) ( Tewary et al., 2011 ). It is possible that the reduced number of inter-subunit interactions in BSMV may explain its lower stability compared with TMV virions ( Makarov et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…The TRV 16 K protein coding sequence was cloned into bacterial expression vector pQE32 (Qiagen, Hilden, Germany) to generate a construct with 16K tagged at the N terminus with 6xHis (16K-His). A construct expressing the plant 6xHis-coilin gene was generated previously (Makarov et al, 2013). Proteins were purified under denaturing conditions using Ni-NTA Qiagen agarose (Qiagen), according to the manufacturer's protocol.…”
Section: Expression and Purification Of The Recombinant Trv 16k Protementioning
confidence: 99%
“…These interactions are believed to determine the stability of tobamovirus virions, which is exceptionally high among helical plant viruses (Makarov et al, 2013).…”
Section: Strong Inter-subunit Interactions In Tobamovirus Virionsmentioning
confidence: 99%
“…In support of this view, the cryoelectron microscopy-based reconstruction of rod-shaped Barley stripe mosaic virus (BSMV, genus Hordeivirus) at a resolution of 19 Å revealed no drastic differences from TMV in the virion structure (Kendall et al, 2013). However, structural studies of the BSMV CP and virions employing analyses of circular dichroism spectra, differential scanning calorimetry and tryptophan spectra have demonstrated that the BSMV virions are considerably more labile than the TMV virions and, in general, the physicochemical characteristics of BSMV virions resemble those of flexuous filamentous viruses rather than TMV (Makarov et al, 2013). The recently reported high-resolution structure of BSMV at 4.1 Å obtained by cryoelectron microscopy (Protein Data Bank accession numbers 5a79 and 5a7a) provides an explanation for this contradiction (Clare et al, 2015).…”
Section: Intermediate Mode Of Subunit Interaction In Hordeivirus Capsidsmentioning
confidence: 99%
See 1 more Smart Citation